PENGARUH PEMBERIAN BRIEF REPETITION ISOMETRIC MAXIMUM EXERCISE DALAM PENCEGAHAN DISUSE ATROFI OTOT PADA PASIEN STROKE NON HEMORAGIK - Dewa Ayu Deni Mahadewi (Coping: Community of Publishing in Nursing, 2014)
Stroke is a disorder in brain function that occurs suddenly due to reduced perfusion of blood flow because clot or infection embolus. Incidence of non-hemorrhagic stroke in 2012 at Badung Hospital was 164 people each year. Generally, the limitations cause by non-hemorrhagic stroke is hemiparesis or weakness so that tend experience disuse of muscle atrophy. Action to prevent disuse of muscle atrophy is by exercise BRIME (Brief Repetition Isometric Maximum Exercise) with number of contraction is 6-12 times for 6-10 seconds. The purpose of this study was to see a big drop in disuse muscle atrophy are experiencing weakness. Therefore it is necessary to conduct research on the effect of BRIME in prevention of disuse of muscle atrophy at non-hemorrhagic stroke patient. This study was applied Quasi-Experimental Design with Non Equivalent Control Group Design. This study was conducted in Oleg in-patient ward of Badung Hospital by number of sample was 14 people who were divided into two groups. Data analysis was applied parametric test that is dependent t-test and independent t-test. The results showed there is no significant difference in the average of muscle circumference between giving of training and BRIME with operasional standard hospital procedure with p = 0,000. The weakness in this study was less strict in controlling of counfounding variable such as nutritional status, neurologic status, physical activity intensity, histology characterictics and muscle histology, etc.